Social Dimension of Sustainable Development and Social Outcomes of Businesses - Merta-Staszczak Adriana; Walecka-Jankowska Katarzyna (Studies in Logic, Grammar and Rhetoric)
The article refers to a valid and current research area related to business sustainability. The development of the concept of sustainability has resulted in the linking of the overall concept to the actions that entrepreneurs take for sustainable development. Thus, it has moved the discussion to the level of sustainable business models, taking into account economic, environmental and social aspects together. The paper focuses on the social layer of the sustainable business model. The main objective of this article is to identify the relationship between activities in the social dimension and sustainable outcomes. Research covers organizations operating in Poland and is based on a questionnaire (the statistical analysis is based on empirical studies conducted in 303 companies operating in Poland). The data collected allowed the construction of a regression model and the results revealed statistically significant relationships between social outcomes and values for society and employees.